Learner’s perspectives and outcomes of peer role play as a teaching learning method for prescription communication skills in second year medical students at a tertiary teaching hospital in India - Asanaliyar, Meharban; Kamath, Latha; Chakraborty, Ananya (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Medical education in India is experiencing a positive shift from traditional curriculum to competency-based medical education. Among the different initiatives, inclusion of role-play with specific aim of improving prescription communication skills in the current curriculum, could lead to beneficial patient- response outcomes. This study aims to evaluate the undergraduate medical student’s perspectives on implementing role-play for learning about prescription communication. Methods: This was a cross-sectional observational study conducted in the department of pharmacology involving second-year medical students of Vydehi institute of medical science and research centre participating for a month-long duration. An internally validated questionnaire was used to assess students’ perspectives on role-play in prescription communication. The outcome was evaluated based on students’ performance in prescription writing and appropriate communication before and after the role-play session. The data obtained was analysed using the SPSS software. Results: The mean score for the overall benefit of role play for prescription communication for all responding participants (n=163) was 4.2 out of 5. In this study, 89.4% of students agreed that role-play in prescription communication should be an essential aspect of their training in the curriculum and is worth taking this additional effort. 84.6% of students found that, the sessions helped to understand and share the pharmacology concepts better. Mean pre and post role play prescription writing assessment scores in students was 7.59 and 9.01 out of 10 respectively. Conclusions: Role-play was well received by the students as a low-cost innovative teaching methodology for better understanding of Pharmacology concepts as mandated by the CBME curriculum. It helps in understanding the importance of teamwork and error-free prescription communication for future clinical practice. Overall, following appropriate demonstration, use of role-play showed significant improvement in student performance in prescription communication.